An all-solid-state aqueous lithium-ion battery and a preparation method thereof
Patent Information
- Application Number
- CN202610809206.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]目前针对全固态锂离子电池的研究主要集中于以锂金属及其合金为为对电极的电池,这类电池在制作过程中对设备和环境要求很高,同时在制作或使用过程中也存在很大的安全隐患,限制全固态电池的发展,基于以上问题,本发明旨在提供一种全固态水系锂离子电池及其制备方法,改善当前全固态锂离子电池在制备和使用过程中存在的问题
[0037](1)本发明的固态电解质及电极浆料的制备均以水作为溶剂,极大降低制备制作成本及对环境的影响。
Smart Images

Figure CN122907741A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to an all-solid-state aqueous lithium-ion battery and its preparation method. Background Technology
[0002] Traditional lithium batteries suffer from safety issues such as leakage, flammability, and explosion. Furthermore, dendrites growing on the lithium anode surface can easily pierce the separator, causing short circuits and potentially leading to thermal runaway. All-solid-state lithium-ion batteries using solid-state electrolytes not only avoid the safety hazards associated with organic liquid electrolytes and prevent dendrites from piercing the separator and causing short circuits, thus solving battery safety problems, but also reduce battery weight and increase energy density. Therefore, developing efficient and applicable solid-state electrolyte materials and corresponding all-solid-state lithium-ion batteries is of great significance to the development of new energy materials and is currently one of the most promising research hotspots.
[0003] Current research on all-solid-state lithium-ion batteries mainly focuses on batteries using lithium metal and its alloys as counter electrodes. These batteries have high requirements for equipment and environment during manufacturing, and also pose significant safety hazards during manufacturing or use, thus limiting the development of all-solid-state batteries. Based on the above problems, this invention aims to provide an all-solid-state aqueous lithium-ion battery and its preparation method, thereby improving the problems existing in the preparation and use of current all-solid-state lithium-ion batteries. Summary of the Invention
[0004] To address the shortcomings of the existing technologies, this invention provides an all-solid-state aqueous lithium-ion battery and its preparation method, aiming to obtain a greener, more environmentally friendly, and more cost-effective lithium-ion battery, thereby improving various safety hazards present in current lithium-ion batteries.
[0005] To achieve the above objectives, the specific technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing an all-solid-state aqueous lithium-ion battery. The all-solid-state aqueous lithium-ion battery comprises three parts: a positive electrode, a solid electrolyte film, and a negative electrode. The positive electrode includes a positive current collector, a positive active material, a conductive agent, and a binder; the negative electrode includes a positive current collector, a positive active material, a conductive agent, and a binder; the raw materials for the solid electrolyte include polyethylene oxide, polyvinylpyrrolidone, cellulose nanofibers, and an ion-conducting agent; the preparation process of the all-solid-state lithium-ion battery includes the following steps:
[0007] An electrolyte solution is prepared using water as a solvent; the raw materials of the electrolyte solution include: polyethylene oxide, polyvinylpyrrolidone, cellulose nanofibers, and ion-conducting agents.
[0008] Using the electrolyte solution as a binder, an electrode slurry is prepared by mixing it with positive or negative active materials and conductive agents in a certain proportion. After vacuum treatment, the slurry is coated onto a current collector and then subjected to a first drying treatment and a first hot pressing treatment to obtain positive and negative electrode sheets, respectively.
[0009] The electrolyte solution is subjected to vacuum treatment, then poured and subjected to a second drying treatment to form an electrolyte thick film; the electrolyte thick film is then cut, stacked and subjected to a second hot pressing treatment to obtain a solid electrolyte thin film.
[0010] The positive electrode, solid electrolyte film, and negative electrode are cut to the same size and assembled into a sandwich battery structure. A third hot pressing process is then performed. The hot-pressed sandwich battery structure is quickly transferred along with the hot pressing mold to a constant temperature chamber set at -60 to 20 ℃ and kept at that temperature for 1-10 min. The sample is then removed from the mold to obtain an all-solid-state aqueous lithium-ion battery.
[0011] Furthermore, in the electrolyte solution, the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:(0.5-10):(0.5-10); the molar ratio of the ionic conductive agent to the vinyl oxide group (-EO-) in polyethylene oxide is 1:(10-30).
[0012] Furthermore, the ionic conductive agent includes, but is not limited to, at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium trifluoromethanesulfonate (LiTf); in one example of the present invention, the ionic conductive agent is lithium bis(trifluoromethanesulfonyl)imide.
[0013] Further, the preparation method of the electrolyte solution is as follows: using water as a solvent, prepare a polyethylene oxide solution, a polyvinylpyrrolidone solution, a cellulose nanofiber solution, and an ion-conducting agent solution respectively; during stirring, add the polyethylene oxide solution, polyvinylpyrrolidone solution, and cellulose nanofiber solution to the ion-conducting agent solution in sequence, with an interval of 30-120 min between each solution addition; after all solutions have been added, seal the container and heat it to 50-90 ℃ and keep it at that temperature for 6-24 h to obtain the electrolyte solution.
[0014] Furthermore, the mass fraction of the polyethylene oxide solution is 2%-6%, the mass fraction of the polyvinylpyrrolidone solution is 2%-6%, the mass fraction of the cellulose nanofiber solution is 2%-6%, and the mass fraction of the ionic conductive agent solution is 3%-20%.
[0015] Furthermore, the mass fraction of the solute in the electrolyte solution is 2%-3%.
[0016] Furthermore, the conditions for the first drying treatment are: 30-50 ℃, 3-12 h.
[0017] Furthermore, the conditions for the first hot pressing treatment are: 40-80 ℃, 1-10 MPa, 1-10 min.
[0018] Furthermore, the positive electrode active material includes, but is not limited to, one of lithium iron phosphate, lithium manganese oxide, and lithium cobalt oxide; in one example of the present invention, the positive electrode material is lithium iron phosphate; the negative electrode active material includes, but is not limited to, one of lithium titanium phosphate, titanium pyrophosphate, and lithium titanium phosphate / titanium pyrophosphate composite material; in one example of the present invention, the negative electrode material is lithium titanium phosphate.
[0019] Furthermore, in the electrode slurry, the mass ratio of electrode (positive or negative) active material, conductive agent and binder is (70-80):10:(10-20).
[0020] Furthermore, the moisture content in the positive and negative electrode sheets is 0.5%-1% (mass fraction).
[0021] Furthermore, the thickness of the electrolyte membrane is 100-500 μm.
[0022] Furthermore, the number of stacked layers is 2-5.
[0023] Furthermore, the thickness of the solid electrolyte film is 10-200 μm.
[0024] Furthermore, the moisture content of the solid electrolyte film is 1%-10% (mass fraction).
[0025] Furthermore, the conditions for the second drying treatment are: 30-50 ℃, 6-12 h.
[0026] Furthermore, the conditions for the second hot pressing treatment are: 60-90 ℃, 1-20 MPa, 2-10 min.
[0027] Furthermore, the conditions for the third hot pressing treatment are: 60-90 ℃, 1-20 MPa, 2-10 min.
[0028] Specifically, the preparation method of the all-solid-state aqueous lithium-ion battery includes the following steps:
[0029] Step S1: Using water as a solvent, prepare a polyethylene oxide solution, a polyvinylpyrrolidone solution, a cellulose nanofiber solution, and an ion-conducting agent solution respectively; the mass fraction of the polyethylene oxide solution is 2%-6%, the mass fraction of the polyvinylpyrrolidone solution is 2%-6%, and the mass fraction of the cellulose nanofiber solution is 2%-6%.
[0030] Step S2: During stirring, polyethylene oxide solution, polyvinylpyrrolidone solution, and cellulose nanofiber solution are added sequentially to the ion-conducting agent solution, with an interval of 30-120 min between each solution addition. After all solutions are added, the container is sealed and heated to 50-90 ℃ and kept at that temperature for 6-24 h to obtain an electrolyte solution. In the electrolyte solution, the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofiber is 100:(0.5-10):(0.5-10); the molar ratio of the ion-conducting agent to the vinyl oxide groups (-EO-) in polyethylene oxide is 1:(10-30).
[0031] Step S3: Using electrolyte solution as a binder, the positive or negative electrode active material, conductive agent, and binder are mixed and stirred evenly in a certain proportion to obtain an electrode slurry. The slurry is then vacuum-treated for 5-20 min, coated onto a current collector, and dried at 30-50 ℃ for 3-12 h. The dried sample is then hot-pressed at 40-80 ℃ under a pressure of 1-10 MPa for 1-10 min. After cooling, positive and negative electrode sheets are obtained respectively. In the electrode slurry, the mass ratio of electrode (positive or negative) active material, conductive agent, and binder is (70-80):10:(10-20). The moisture content in the positive and negative electrode sheets is 0.5%-1% (mass fraction).
[0032] Step S4: Vacuum treat the electrolyte solution for 5-30 min, then pour it into the mold. Place the mold in a drying oven at 30-50 ℃ for 6-12 h. After demolding, a solid electrolyte film with a thickness of 100-500 μm is obtained.
[0033] Step S5: Cut the solid electrolyte thick film into electrolyte sheets of the same size, stack 2-5 layers of electrolyte sheets and then perform hot pressing treatment. The hot pressing temperature is 60-90 ℃, the pressure is 1-20 MPa, and the holding time is 2-10 min to obtain a solid electrolyte film with a thickness of 10-200 μm; the moisture content of the solid electrolyte film is 1%-10% (mass fraction).
[0034] Step S6: Cut the positive electrode, negative electrode and solid electrolyte film described in step S3 to the same size and stack them into a sandwich battery structure. Hold the sandwich battery structure at 60-90 ℃ and 1-20 MPa pressure for 2-10 min. Quickly transfer the sandwich battery structure with the hot-pressing mold to a constant temperature chamber set at -60 to 20 ℃ and keep it at that temperature for 1-10 min. Take the sample out of the mold to obtain an all-solid-state aqueous lithium-ion battery.
[0035] Secondly, the present invention provides an all-solid-state aqueous lithium-ion battery prepared using the aforementioned preparation method.
[0036] Compared with the prior art, the advantages of the present invention are:
[0037] (1) The solid electrolyte and electrode slurry of the present invention are prepared using water as a solvent, which greatly reduces the preparation cost and the impact on the environment.
[0038] (2) The all-solid-state battery provided by the present invention allows for the reasonable presence of water, which improves battery performance while greatly reducing the requirements for equipment and environment during battery preparation.
[0039] (3) The all-solid-state lithium-ion battery solution provided by the present invention largely avoids the safety hazards (such as flammability, easy failure, etc.) that exist in the preparation and use of traditional lithium-ion batteries and existing all-solid-state batteries. Attached Figure Description
[0040] Figure 1 This is a flowchart illustrating the preparation process of the all-solid-state aqueous lithium-ion battery of this invention.
[0041] Figure 2 The cyclic voltammetry curves of the all-solid-state aqueous lithium-ion battery in Example 1 are shown.
[0042] Figure 3 Cyclic voltammetry curves of the all-solid-state aqueous lithium-ion batteries in Examples 1-8;
[0043] Figure 4 The charge-discharge curves of the all-solid-state aqueous lithium-ion battery in Example 1 are shown.
[0044] Figure 5 The cycling performance curves are for the all-solid-state aqueous lithium-ion batteries of Examples 1-8. Detailed Implementation
[0045] To enable those skilled in the art to clearly and completely understand the technical solution of the present invention, the present invention will be further described in detail below with reference to embodiments. Obviously, the embodiments described herein are only for explaining the present invention and are not intended to limit the scope of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0046] This invention provides a method for preparing an all-solid-state aqueous lithium-ion battery, comprising the following steps:
[0047] An electrolyte solution is prepared using water as a solvent; the raw materials of the electrolyte solution include: polyethylene oxide, polyvinylpyrrolidone, cellulose nanofibers, and ion-conducting agents.
[0048] Using the electrolyte solution as a binder, an electrode slurry is prepared by mixing it with positive or negative active materials and conductive agents in a certain proportion. After vacuum treatment, the slurry is coated onto a current collector and then subjected to a first drying treatment and a first hot pressing treatment to obtain positive and negative electrode sheets, respectively.
[0049] The electrolyte solution is subjected to vacuum treatment, then poured and subjected to a second drying treatment to form an electrolyte thick film; the electrolyte thick film is then cut, stacked and subjected to a second hot pressing treatment to obtain a solid electrolyte thin film.
[0050] The positive electrode, solid electrolyte film, and negative electrode are cut to the same size and assembled into a sandwich battery structure. A third hot pressing process is then performed. The hot-pressed sandwich battery structure is quickly transferred along with the hot pressing mold to a constant temperature chamber set at -60 to 20 ℃ and kept at that temperature for 1-10 min. The sample is then removed from the mold to obtain an all-solid-state aqueous lithium-ion battery.
[0051] In some examples, the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers in the electrolyte solution is 100:(0.5-10):(0.5-10); and the molar ratio of the ionic conductive agent to the vinyl oxide group (-EO-) in polyethylene oxide is 1:(10-30).
[0052] In some examples, the ionic conductive agent includes, but is not limited to, at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium trifluoromethanesulfonate (LiTf).
[0053] In some examples, the conditions for the first drying treatment are: 30-50 ℃, 3-12 h; and the conditions for the first hot pressing treatment are: 40-80 ℃, 2-10 MPa, 1-10 min.
[0054] In some examples, the positive electrode active material includes, but is not limited to, one of lithium iron phosphate, lithium manganese oxide, and lithium cobalt oxide; the negative electrode active material includes, but is not limited to, one of lithium titanium phosphate, titanium pyrophosphate, and lithium titanium phosphate / titanium pyrophosphate composite materials.
[0055] In some examples, the mass ratio of electrode (positive or negative) active material, conductive agent and binder in the electrode slurry is (70-80):10:(10-20).
[0056] In some examples, the moisture content in the positive and negative electrode sheets is 0.5%-1% (mass fraction).
[0057] In some examples, the thickness of the electrolyte membrane is 100-500 μm.
[0058] In some examples, the number of stacked layers is 2-5. This invention improves the performance of electrolyte membranes and increases the efficiency of electrolyte membrane fabrication through a stacking-hot-pressing method.
[0059] In some examples, the thickness of the solid electrolyte film is 10-200 μm.
[0060] In some examples, the moisture content of the solid electrolyte membrane is 1%-10% (mass fraction).
[0061] In some examples, the conditions for the second drying treatment are: 30-50 ℃, 6-12 h; and the conditions for the second hot pressing treatment are: 60-90 ℃, 5-20 MPa, 2-10 min.
[0062] In some examples, the conditions for the third hot pressing treatment are: 60-90 °C, 1-20 MPa, 2-10 min.
[0063] In the following specific embodiments, the preparation method of the all-solid-state aqueous lithium-ion battery is as follows: Figure 1 As shown, the steps are as follows:
[0064] Step S1: Using water as a solvent, prepare a polyethylene oxide solution, a polyvinylpyrrolidone solution, a cellulose nanofiber solution, and an ion-conducting agent solution respectively; the mass fraction of the polyethylene oxide solution is 2%-6%, the mass fraction of the polyvinylpyrrolidone solution is 2%-6%, the mass fraction of the cellulose nanofiber solution is 2%-6%, and the mass fraction of the ion-conducting agent solution is 3%-20%.
[0065] Step S2: During stirring, the polyethylene oxide solution, polyvinylpyrrolidone solution, and cellulose nanofiber solution are added sequentially to the ion-conducting agent solution, with an interval of 30-120 min between each solution addition. After all solutions are added, the container is sealed and heated to 50-90 ℃ and kept at that temperature for 6-24 h to obtain the electrolyte solution. In the electrolyte solution, the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:(0.5-10):(0.5-10); the molar ratio of the ion-conducting agent to the vinyl oxide groups (-EO-) in polyethylene oxide is 1:(10-30). This invention prepares each component into a solution separately and then mixes them in a specific order to form the electrolyte solution. This operation effectively improves the dispersibility of each substance in water. If the solid powder of the corresponding component is directly added to water to prepare the electrolyte solution, poor dispersibility will lead to agglomeration.
[0066] Step S3: Using electrolyte solution as a binder, the positive or negative electrode active material, conductive agent, and binder are mixed and stirred evenly in a certain proportion to obtain an electrode slurry. The slurry is then vacuum-treated for 5-20 min, coated onto a current collector, and dried at 30-50 ℃ for 3-12 h. The dried sample is then hot-pressed at 40-80 ℃ under a pressure of 1-10 MPa for 1-10 min. After cooling, positive and negative electrode sheets are obtained respectively. In the electrode slurry, the mass ratio of electrode (positive or negative) active material, conductive agent, and binder is (70-80):10:(10-20). The moisture content in the positive and negative electrode sheets is 0.5%-1% (mass fraction).
[0067] Step S4: Vacuum treat the electrolyte solution for 5-30 min, then pour it into a mold. Place the mold in a drying oven at 30-50 ℃ for 6-12 h. After demolding, a solid electrolyte film with a thickness of 100-500 μm is obtained. The vacuum treatment can eliminate air bubbles in the solution to avoid the problem of poor density of the solid electrolyte film.
[0068] Step S5: Cut the solid electrolyte thick film into electrolyte sheets of the same size, stack 2-5 layers of electrolyte sheets and then perform hot pressing treatment. The hot pressing temperature is 60-90 ℃, the pressure is 1-20 MPa, and the holding time is 2-10 min to obtain a solid electrolyte film with a thickness of 10-200 μm; the moisture content of the solid electrolyte film is 1%-10% (mass fraction).
[0069] Step S6: Cut the positive electrode, negative electrode and solid electrolyte film described in step S3 to the same size and stack them into a sandwich battery structure. Hold the sandwich battery structure at 60-90 ℃ and 1-20 MPa pressure for 2-10 min. Quickly transfer the sandwich battery structure with the hot-pressing mold to a constant temperature chamber set at -60 to 20 ℃ and keep it at that temperature for 1-10 min. Take the sample out of the mold to obtain an all-solid-state aqueous lithium-ion battery.
[0070] Example 1
[0071] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0072] Step 1, Preparation of raw material solution:
[0073] Using deionized water as a solvent, solutions of polyethylene oxide (3% by mass), polyvinylpyrrolidone (3% by mass), cellulose nanofibers (3% by mass), and lithium bis(trifluoromethanesulfonyl)imide (5% by mass) were prepared respectively.
[0074] Step 2, Preparation of electrolyte solution:
[0075] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:20, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers was 100:5:0.5.
[0076] Step 3, Preparation of positive and negative electrode plates:
[0077] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0078] The positive / negative active materials were mixed with a conductive agent and a binder to obtain an electrode slurry. The slurry was vacuum treated for 10 minutes and then coated onto a current collector. The slurry was dried at 50 °C for 8 hours. The dried sample was then hot-pressed at 70 °C with a pressure of 2 MPa for 5 minutes. After cooling, the positive and negative electrode sheets were obtained. The moisture content of the positive and negative electrode sheets was 0.5%.
[0079] Step 4, Preparation of the electrolyte thick film:
[0080] After the electrolyte solution obtained in step 2 was vacuum treated for 10 min, it was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 300 μm.
[0081] Step 5, Preparation of the electrolyte film:
[0082] The electrolyte thick film obtained in step 4 is cut into circular pieces with a diameter of 20 mm. Five circular electrolyte thick films are stacked and held at 80 °C and 2 MPa for 2 min to obtain a solid electrolyte film with a thickness of about 150 μm. The moisture content of the solid electrolyte film is 1%.
[0083] Step 6, Fabrication of an all-solid-state aqueous lithium-ion battery:
[0084] After assembling the electrolyte film obtained in step 5 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0085] Example 2
[0086] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:5:5.
[0087] Example 3
[0088] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:5:2.5.
[0089] Example 4
[0090] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:2.5:2.5.
[0091] Example 5
[0092] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:2.5:2.5. In step 5, after stacking 5 disc electrolyte films, a solid electrolyte film with a thickness of about 100 μm is obtained by maintaining it at 80 °C and 4 MPa for 2 min.
[0093] Example 6
[0094] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:5:2.5. In step 5, after stacking 5 disc electrolyte films, a solid electrolyte film with a thickness of about 100 μm is obtained by maintaining it at 80 °C and 4 MPa for 2 min.
[0095] Example 7
[0096] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:2.5:5. In step 5, after stacking 5 disc electrolyte films, a solid electrolyte film with a thickness of about 100 μm is obtained by maintaining it at 80 °C and 4 MPa for 2 min.
[0097] Example 8
[0098] The preparation steps of the all-solid-state aqueous lithium-ion battery in this embodiment are basically the same as those in Example 1. The difference is that in step 2, the molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte solution is 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:5:5. In step 5, after stacking 5 disc electrolyte films, the solid electrolyte film with a thickness of about 100 μm is obtained by maintaining it at 80 °C and 4 MPa for 2 min.
[0099] Comparative Example 1
[0100] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0101] Step 1, Preparation of raw material solution:
[0102] Using deionized water as a solvent, solutions of polyethylene oxide (3% by mass), polyvinylpyrrolidone (3% by mass), cellulose nanofibers (3% by mass), and lithium bis(trifluoromethanesulfonyl)imide (5% by mass) were prepared respectively.
[0103] Step 2, Preparation of electrolyte solution:
[0104] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers was 100:10:10.
[0105] Step 3, Preparation of positive and negative electrode plates:
[0106] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0107] The positive / negative active materials were mixed with a conductive agent and a binder to obtain an electrode slurry. The slurry was vacuum treated for 10 minutes and then coated onto a current collector. The slurry was dried at 50 °C for 8 hours. The dried sample was then hot-pressed at 70 °C with a pressure of 2 MPa for 5 minutes. After cooling, the positive and negative electrode sheets were obtained. The moisture content of the positive and negative electrode sheets was 0.5%.
[0108] Step 4, Preparation of the electrolyte thick film:
[0109] After vacuum treatment for 10 min, the electrolyte solution obtained in step 2 was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 100 μm.
[0110] Step 5, Preparation of all-solid-state aqueous lithium-ion batteries:
[0111] After assembling the electrolyte thick film obtained in step 4 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa pressure for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0112] Comparative Example 2
[0113] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0114] Step 1, Preparation of raw material solution:
[0115] Using deionized water as a solvent, solutions of polyethylene oxide (3% by mass), polyvinylpyrrolidone (3% by mass), cellulose nanofibers (3% by mass), and lithium bis(trifluoromethanesulfonyl)imide (5% by mass) were prepared respectively.
[0116] Step 2, Preparation of electrolyte solution:
[0117] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers was 100:5:2.5.
[0118] Step 3, Preparation of positive and negative electrode plates:
[0119] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0120] The positive / negative active materials were mixed with a conductive agent and a binder to obtain an electrode slurry. The slurry was vacuum treated for 10 minutes and then coated onto a current collector. The slurry was dried at 50 °C for 8 hours. The dried sample was then hot-pressed at 70 °C with a pressure of 2 MPa for 5 minutes. After cooling, the positive and negative electrode sheets were obtained. The moisture content of the positive and negative electrode sheets was 0.5%.
[0121] Step 4, Preparation of the electrolyte thick film:
[0122] After vacuum treatment for 10 min, the electrolyte solution obtained in step 2 was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 100 μm.
[0123] Step 5, Preparation of all-solid-state aqueous lithium-ion batteries:
[0124] After assembling the electrolyte thick film obtained in step 4 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa pressure for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0125] Comparative Example 3
[0126] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0127] Step 1, Preparation of raw material solution:
[0128] Using deionized water as a solvent, solutions of polyethylene oxide (3% by mass), polyvinylpyrrolidone (3% by mass), cellulose nanofibers (3% by mass), and lithium bis(trifluoromethanesulfonyl)imide (5% by mass) were prepared respectively.
[0129] Step 2, Preparation of electrolyte solution:
[0130] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers was 100:5:2.5.
[0131] Step 3, Preparation of positive and negative electrode plates:
[0132] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0133] The positive / negative active materials were mixed with a conductive agent and a binder to obtain an electrode slurry. The slurry was vacuum treated for 10 minutes and then coated onto a current collector. The slurry was dried at 50 °C for 8 hours. The dried sample was then hot-pressed at 70 °C with a pressure of 2 MPa for 5 minutes. After cooling, the positive and negative electrode sheets were obtained. The moisture content of the positive and negative electrode sheets was 0.5%.
[0134] Step 4, Preparation of the electrolyte thick film:
[0135] After the electrolyte solution obtained in step 2 was vacuum treated for 10 min, it was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 300 μm.
[0136] Step 5, Preparation of the electrolyte film:
[0137] The electrolyte thick film obtained in step 4 is pressed at 80 °C to form a solid electrolyte film with a thickness of about 100 μm.
[0138] Step 6, Fabrication of an all-solid-state aqueous lithium-ion battery:
[0139] After assembling the electrolyte film obtained in step 5 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0140] Comparative Example 4
[0141] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0142] Step 1, Preparation of raw material solution:
[0143] Using deionized water as a solvent, solutions of polyethylene oxide (3% by mass), cellulose nanofibers (3% by mass), and lithium bis(trifluoromethanesulfonyl)imide (5% by mass) were prepared respectively.
[0144] Step 2, Preparation of electrolyte solution:
[0145] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:20, and the mass ratio of polyethylene oxide to cellulose nanofibers was 100:7.5.
[0146] Step 3, Preparation of positive and negative electrode plates:
[0147] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0148] The positive / negative active materials were mixed with a conductive agent and a binder to obtain an electrode slurry. The slurry was vacuum treated for 10 minutes and then coated onto a current collector. The slurry was dried at 50 °C for 8 hours. The dried sample was then hot-pressed at 70 °C with a pressure of 2 MPa for 5 minutes. After cooling, the positive and negative electrode sheets were obtained. The moisture content of the positive and negative electrode sheets was 0.5%.
[0149] Step 4, Preparation of the electrolyte thick film:
[0150] After the electrolyte solution obtained in step 2 was vacuum treated for 10 min, it was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 300 μm.
[0151] Step 5, Preparation of the electrolyte film:
[0152] The electrolyte thick film obtained in step 4 was cut into circular pieces with a diameter of 20 mm. Five circular electrolyte thick films were stacked and held at 80 °C with a pressure of 4 MPa for 2 min to obtain a solid electrolyte film with a thickness of about 100 μm.
[0153] Step 6, Fabrication of an all-solid-state aqueous lithium-ion battery:
[0154] After assembling the electrolyte film obtained in step 5 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0155] Comparative Example 5
[0156] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0157] Step 1, Preparation of raw material solution:
[0158] Using deionized water as a solvent, solutions of polyethylene oxide (3% by mass), polyvinylpyrrolidone (3% by mass), and lithium bis(trifluoromethanesulfonyl)imide (5% by mass) were prepared respectively.
[0159] Step 2, Preparation of electrolyte solution:
[0160] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:20, and the mass ratio of polyethylene oxide to polyvinylpyrrolidone was 100:7.5.
[0161] Step 3, Preparation of positive and negative electrode plates:
[0162] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0163] The positive / negative active materials were mixed with a conductive agent and a binder to obtain an electrode slurry. The slurry was vacuum treated for 10 minutes and then coated onto a current collector. The slurry was dried at 50 °C for 8 hours. The dried sample was then hot-pressed at 70 °C with a pressure of 2 MPa for 5 minutes. After cooling, the positive and negative electrode sheets were obtained. The moisture content of the positive and negative electrode sheets was 0.5%.
[0164] Step 4, Preparation of the electrolyte thick film:
[0165] After the electrolyte solution obtained in step 2 was vacuum treated for 10 min, it was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 300 μm.
[0166] Step 5, Preparation of the electrolyte film:
[0167] The electrolyte thick film obtained in step 4 was cut into circular pieces with a diameter of 20 mm. Five circular electrolyte thick films were stacked and held at 80 °C with a pressure of 4 MPa for 2 min to obtain a solid electrolyte film with a thickness of about 100 μm.
[0168] Step 6, Fabrication of an all-solid-state aqueous lithium-ion battery:
[0169] After assembling the electrolyte film obtained in step 5 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0170] Comparative Example 6
[0171] A fully solid-state aqueous lithium-ion battery is prepared by the following steps:
[0172] Step 2, Preparation of electrolyte solution:
[0173] A lithium bis(trifluoromethanesulfonyl)imide solution was taken, and while stirring, a polyethylene oxide solution, a polyvinylpyrrolidone solution, and a cellulose nanofiber solution were added to the lithium bis(trifluoromethanesulfonyl)imide solution in sequence, with an interval of 30 min between each solution addition. After all solutions were added, the container was sealed and heated to 60 °C and kept at that temperature for 6 h to obtain an electrolyte gel. The molar ratio of lithium ions to vinyl oxide groups (-EO-) in the electrolyte gel was 1:15, and the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers was 100:5:2.5.
[0174] Step 3, Preparation of positive and negative electrode plates:
[0175] Using the electrolyte solution obtained in step 2 as a binder, lithium iron phosphate and lithium titanium phosphate as positive and negative electrode active materials, respectively, and carbon nanotubes as a conductive agent, positive and negative electrode sheets are prepared; the mass ratio of positive / negative electrode active materials, conductive agent and binder is 70:10:20.
[0176] The positive / negative active materials are mixed with conductive agent and binder to obtain electrode slurry. The slurry is vacuum treated for 10 min, coated onto current collector, dried at 50 ℃ for 8 h, and then cooled to obtain positive and negative electrode sheets.
[0177] Step 4, Preparation of the electrolyte thick film:
[0178] After the electrolyte solution obtained in step 2 was vacuum treated for 10 min, it was poured into a polytetrafluoroethylene mold and heat-treated at 50°C for 12 h before being removed to obtain an electrolyte film with a thickness of 300 μm.
[0179] Step 5, Preparation of the electrolyte film:
[0180] The electrolyte thick film obtained in step 4 was cut into circular pieces with a diameter of 20 mm. Five circular electrolyte thick films were stacked and held at 80 °C with a pressure of 4 MPa for 4 min to obtain a solid electrolyte film with a thickness of about 100 μm.
[0181] Step 6, Fabrication of an all-solid-state aqueous lithium-ion battery:
[0182] After assembling the electrolyte thick film obtained in step 5 between the positive and negative electrode sheets obtained in step 3 into a sandwich structure, the battery is kept at 60 °C and 2 MPa pressure for 5 min to obtain an all-solid-state aqueous lithium-ion battery.
[0183] The performance of the all-solid-state lithium-ion batteries prepared in Examples 1-8 and Comparative Examples 1-6 is shown in Table 1. The test results are the 1C performance under room temperature conditions.
[0184] Table 1: Performance Test Results of All-Solid-State Lithium-ion Batteries
[0185]
[0186] Figure 2 The figure shows the cyclic voltammetry curves of the all-solid-state aqueous lithium-ion battery of Example 1. As can be seen from the figure, the voltage plateau of the positive electrode lithium iron phosphate (LFP) used in the all-solid-state battery is about 2.5V, the voltage plateau of the negative electrode lithium titanium phosphate (LTP) is about 3.5V, and the voltage plateau difference between the positive and negative electrodes is about 1.0V.
[0187] Figure 3 The figures show the cyclic voltammograms of the all-solid-state aqueous lithium-ion batteries of Examples 1-8; it can be seen from the figures that the voltage plateau of the all-solid-state lithium-ion battery using the present invention is approximately 1.0 V, compared to... Figure 2 The voltage plateau difference between the positive and negative electrodes is shown. The introduction of additives into the electrolyte reduces the potential difference between the redox peaks. However, if too much additive is added, the potential difference between the redox peaks will increase, which will reduce the cycle performance of the battery.
[0188] Figure 4 The figure shows the charge-discharge curves of the all-solid-state aqueous lithium-ion battery of Example 1. As can be seen from the figure, the charge-discharge curves of the all-solid-state battery have relatively stable plateaus, with both charge and discharge voltage plateaus around 1.0 V. Figure 1 and Figure 2 The results shown correspond.
[0189] Figure 5 The table shows the cycle performance curves of the all-solid-state aqueous lithium-ion batteries in Examples 1-8. As can be seen from Table 1, the introduction of additives into the solid electrolyte improves the capacity and stability of the all-solid-state battery, but the introduction of excessive additives (Comparative Example 1) actually degrades the battery's performance.
[0190] In summary, this invention uses water as a solvent to prepare an electrolyte solution comprising polyethylene oxide, polyvinylpyrrolidone, cellulose nanofibers, and an ion-conducting agent. The electrolyte solution is then poured and dried to form a thick electrolyte film, which is subsequently stacked and hot-pressed to form a thin electrolyte film. Simultaneously, using the electrolyte solution as a binder, an electrode slurry is prepared by mixing the positive or negative electrode active material and a conductive agent in a specific ratio, followed by vacuum treatment. This slurry is coated onto a current collector, dried, and hot-pressed to form positive and negative electrode sheets. The electrolyte film is then placed between the positive and negative electrode sheets and hot-pressed to obtain a fully solid-state aqueous lithium-ion battery. This fully solid-state aqueous lithium-ion battery exhibits excellent safety performance and cycle stability, avoiding the safety hazards present in the preparation and use of traditional lithium-ion batteries and existing fully solid-state batteries.
[0191] The above detailed embodiments describe the implementation of the present invention; however, the present invention is not limited to the specific details described in the above embodiments. Within the scope of the claims and technical concept of the present invention, various simple modifications and changes can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing an all-solid-state aqueous lithium-ion battery, characterized in that, Includes the following steps: An electrolyte solution is prepared using water as a solvent; the raw materials of the electrolyte solution include: polyethylene oxide, polyvinylpyrrolidone, cellulose nanofibers, and ion-conducting agents. Using the electrolyte solution as a binder, an electrode slurry is prepared by mixing it with positive or negative active materials and conductive agents in a certain proportion. After vacuum treatment, the slurry is coated onto a current collector and then subjected to a first drying treatment and a first hot pressing treatment to obtain positive and negative electrode sheets, respectively. The electrolyte solution is subjected to vacuum treatment, then poured and subjected to a second drying treatment to form an electrolyte thick film; the electrolyte thick film is then cut, stacked and subjected to a second hot pressing treatment to obtain a solid electrolyte thin film. The positive electrode, solid electrolyte film, and negative electrode are cut to the same size. The solid electrolyte film is placed between the positive and negative electrode to assemble a sandwich battery structure. A third hot-pressing treatment is then performed to obtain an all-solid-state aqueous lithium-ion battery.
2. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 1, characterized in that, In the electrolyte solution, the mass ratio of polyethylene oxide, polyvinylpyrrolidone, and cellulose nanofibers is 100:(0.5-10):(0.5-10); the molar ratio of the ionic conductive agent to the vinyl oxide groups in polyethylene oxide is 1:(10-30).
3. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 2, characterized in that, The ionic conductive agent includes, but is not limited to, at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium trifluoromethanesulfonate.
4. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 2, characterized in that, The electrolyte solution is prepared as follows: using water as a solvent, polyethylene oxide solution, polyvinylpyrrolidone solution, cellulose nanofiber solution, and ion-conducting agent solution are prepared respectively. During the stirring process, polyethylene oxide solution, polyvinylpyrrolidone solution, and cellulose nanofiber solution are added to the ion-conducting agent solution in sequence, with an interval of 30-120 min between each solution addition. After all solutions have been added, the container is sealed and heated to 50-90 ℃ and kept at that temperature for 6-24 h to obtain the electrolyte gel.
5. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 1, characterized in that, The conditions for the first drying treatment are: 30-50 ℃, 3-12 h; the conditions for the first hot pressing treatment are: 40-80 ℃, 1-10 MPa, 1-10 min.
6. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 1, characterized in that, In the electrode slurry, the mass ratio of positive / negative active material, conductive agent and binder is (70-80):10:(10-20).
7. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 1, characterized in that, The number of stacked layers is 2-5.
8. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 1, characterized in that, The conditions for the second drying treatment are: 30-50 ℃, 6-12 h; the conditions for the second hot pressing treatment are: 60-90 ℃, 1-20 MPa, 2-10 min.
9. The method for preparing an all-solid-state aqueous lithium-ion battery according to claim 1, characterized in that, The conditions for the third hot pressing treatment are: 60-90 ℃, 1-20 MPa, 2-10 min.
10. An all-solid-state aqueous lithium-ion battery prepared by the preparation method according to any one of claims 1-9.